Exploration of the tick-Borrelia molecular interactions by employing the transcriptomic approaches - Mahmood, Sazzad (Jihočeská univerzita, 2021)
Along with climate change and increased sharing of habitat, ticks are coming into more frequent contact with humans. The hard tick Ixodes scapularis and Ixodes ricinus are known disease vectors in Northern America and Europe, respectively. Along with many other pathogenic microorganisms, these ticks spread Borrelia sp. by ectoparasitic blood feeding. Borrelia afzelii is the major European Lyme disease pathogen spread by I. ricinus. Our study focuses on differential gene expression in I. ricinus salivary gland and midgut, induced in the nymphal stage by B. afzelii infection. Tick genes upregulated by infection are considered to play essential roles for the acquisition, persistence, and transmission of Borrelia. We have determined 32,897 full length sequences of tick mRNA from B. afzelii infected/noninfected tick salivary glands and the whole body. In addition, we have obtained MACEseq (Massive Analysis of cDNA Ends) from both midgut and salivary glands while the nymphs were non-infected or infected with B. afzelii during three different phases of blood-feeding. From the MACE database, we obtained 250-500 bp 3'-end sequences with raw quantitative expression values. Total reads, unique sequences and protein coding tick genes from midgut samples were 38,199,641, 88,825 and 24,276, and from salivary gland were 74,651,134, 93,096 and 26,179, respectively. After filtering, using several criteria, expression was validated by qPCR. Hence, the validated genes may most likely interact with Borrelia in its acquisition, persistence, or transmission to the vertebrate host. In our study, RNA interference approaches and vaccination were implemented in order to investigate the impact of upregulated tick midgut and salivary gland genes on Borrelia transmission to C3H mice.
Exploration of the tick-Borrelia molecular interactions by employing the transcriptomic approaches
Keywords: Ixodes ricinus; Borrelia afzelii; Tick; Lyme disease; Borreliosis; Midgut; Salivary glands; Transcriptomics; Borrelia transmission; RNAi; Mouse immunization; Massive Analysis of cDNA Ends (MACE); Ixodes ricinus; Borrelia afzelii; Tick; Lyme disease; Borreliosis; Midgut; Salivary glands; Transcriptomics; Borrelia transmission; RNAi; Mouse immunization; Massive Analysis of cDNA Ends (MACE)